A heart so green - Selene, Lyra (Selene, Lyra. Fair Folk, 2026)
"After the explosive finale of the Tournament of Kings, Fia and Irian manage to escape to the wildlands, dodging pursuit by Fia's cunning sister Eala. With Fia locked in her own mind, battling a powerful celestial entity; Irian must form new alliances to come up with a plan to defeat Eala's terrifying magic. With both the human and fae realm under threat, Fia and Irian must pursue their dangerous plan, no matter the cost. On Bealtain Eve, when the veil between worlds is at its thinnest, they will finally face off against the swan princess and forge the ending to their love story that was written in the stars"-- Provided by publisher.